(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article includes deep analysis of the higher education system of the Republic of Belarus. В Беларуси остро стоит вопрос падения числа студентов. This is due to the departure of students abroad for training and demographic problems. There is a significant decline in fertility in 1995-2000. This is due to the economic crisis in Belarus at this time. The second problem facing universities of Belarus is the decline in the number of candidates and doctors of science, low motivation of young people to work in science. These moments open the question of finding new methods of popularizing educational services. One of these areas to solve these problems may be improving the work of the university site. In the course of the study, the author of the article found that, in most cases, students take information about a higher education institution from the Internet. They are actively exploring the websites of universities. Make your choice based on the university’s rating. This includes Webometrics ranking. Therefore, a way to improve the elements contributing to the growth of Webometrics ranking should be a tool for promoting educational services. The Webometrics ranking of universities in the world is an initiative of Cybermetrics Lab, the research group Centro de Ciencias Humanas of Sociales (CCHS), a member of the National Research Council (CSIC), the largest organization in the field of research in Spain. The highest positions in this ranking in Belarus usually took the Belarusian State University. Brest State Technical University ranks is 11th place in Belarus. To ensure growth in this ranking, the university needs to increase quotation of articles and the number of users of the site. The author also explored the issue of popularization the educational services (on the example of Brest State Technical University) through the use of web-technologies. In particular, one of the directions is to improve the level of site of the university, and also increase a number of users of the site. At the end the implementation of these activities should increase the position of the university in the ranking of Webometrics.